Spine health: Back pain and deformity progression - Chinmay S. Paranjape, MD, MHSc; Michelle C. Welborn, MD (Elsevier, 2024)
Back pain and spinal deformity arising from a variety of etiologies are closely linked to alterations in bone health. This review is intended to summarize the known processes for each of these conditions that negatively impact bone health. It will then elucidate how poor bone quality can further worsen deformity. Finally, it will discuss how interventions targeting improvement in bone health may affect treatment and progression of deformity. Key Concepts: (1) Back pain is highly prevalent affecting up to a third of adolescents and is even more so in patients who are vitamin D deficient. (2) Scoliosis patients from various etiologies all experience higher rates of back pain and tend to have lower bone mineral density than their healthy pediatric peers. (3) There is an interplay between deformity and bone health, where deformity can both drive and be driven by bone health. (4) Treatments targeting bone health may positively affect both natural history and surgical outcomes for patients who have scoliosis with various underlying etiologies. (5) Further research is needed to elucidate mechanistic pathways that link bone health to deformity and to evaluate targets for therapy.